How Could Trade Measures Being Considered to Mitigate Climate Change Affect LDC Exports? - Jensen, Michael Friis (World Bank, Washington, DC, 2021)
Export led growth remains a critical route out of poverty for many least developed countries (LDCs). But in a world increasingly concerned about climate change and the contribution of international trade to global warming will measures being considered to mitigate emissions hurt the export opportunities of LDCs? This paper reviews the trade-related instruments being considered by both policymakers and business communities to mitigate climate change, identifying areas where LDCs may be affected. The paper explores the following key issues: (i) how a shift to low carbon transportation may affect LDC exports given their remote location from main markets; (ii) how LDCs’ exports will be influenced by their own domestic climate measures; (iii) whether mitigation instruments introduced by other governments that result in carbon border tax adjustments will significantly affect LDC exports; (iv) the importance of the nature of liberalization of trade in green goods; (v) how government sustainability standards in overseas market may affect trade, and finally (vi) the potential impact of private measures used by businesses for carbon management. The paper shows how climate change mitigation instruments will create challenges and provide new opportunities for LDC exports that will require attention to traditional trade policy issues but also to a deeper agenda relating to regulatory development and convergence.